Pemikiran Harun Nasution Terhadap Pendidikan Dan Relevansinya Dengan Dunia Pendidikan Islam Era Modern - Danil Hakim Maulidi; Maragustam; Insiyatul Fikriyah (Al-Abshor : Jurnal Pendidikan Agama Islam, 2026)
Abstract This research falls within the realm of Islamic educational thought, focusing on the analysis of Harun Nasution's ideas, with a religious-rational character, and their relevance to the development of contemporary Islamic education. Harun Nasution places moral education as the main core of religious education, emphasizing not merely the mastery of religious knowledge and the performance of religious rituals, but also the process of internalizing moral values ​​in individual life. Religious education, in his view, must be able to shape students' ethical awareness regarding the categories of good and bad in human behavior, thereby producing individuals who are socially and spiritually responsible. This research uses a library study method with a qualitative approach, through a critical review of Harun Nasution's works and various relevant literature in the field of Islamic education. The results of the study indicate that Harun Nasution's religious-rational thought emphasizes the importance of reason in understanding Islamic teachings, without neglecting revelation as the primary source of truth. He seeks to integrate rationality with religious values, thus creating a more open and dialogical understanding of Islam regarding the development of science. Thus, Harun Nasution's thinking makes a significant contribution to building an adaptive, contextual, and progressive paradigm of Islamic education. This approach allows Islamic education to remain relevant in facing the challenges of the modern era, while maintaining the fundamental values ​​of Islamic teachings as the main foundation in the formation of human character and civilization. Abstrak Penelitian ini berada dalam ranah kajian pemikiran pendidikan Islam yang berfokus pada analisis gagasan Harun Nasution dengan corak religius-rasional serta relevansinya dalam pengembangan pendidikan Islam kontemporer. Harun Nasution menempatkan pendidikan moral sebagai inti utama dalam pendidikan agama, yang tidak semata-mata menekankan pada penguasaan pengetahuan keagamaan dan pelaksanaan ritual ibadah, tetapi lebih jauh pada proses internalisasi nilai-nilai moral dalam kehidupan individu. Pendidikan agama, dalam pandangannya, harus mampu membentuk kesadaran etis peserta didik mengenai kategori baik dan buruk dalam perilaku manusia, sehingga melahirkan pribadi yang bertanggung jawab secara sosial dan spiritual. Penelitian ini menggunakan metode studi kepustakaan dengan pendekatan kualitatif, melalui kajian kritis terhadap karya-karya Harun Nasution serta berbagai literatur yang relevan dalam bidang pendidikan Islam. Hasil kajian menunjukkan bahwa pemikiran religius-rasional Harun Nasution menegaskan pentingnya peran akal dalam memahami ajaran Islam, tanpa mengesampingkan wahyu sebagai sumber utama kebenaran. Ia berupaya mengintegrasikan rasionalitas dengan nilai-nilai keagamaan sehingga tercipta pemahaman Islam yang lebih terbuka dan dialogis terhadap perkembangan ilmu pengetahuan. Dengan demikian, pemikiran Harun Nasution memberikan kontribusi signifikan dalam membangun paradigma pendidikan Islam yang adaptif, kontekstual, dan progresif. Pendekatan ini memungkinkan pendidikan Islam untuk tetap relevan dalam menghadapi tantangan zaman modern, sekaligus mempertahankan nilai-nilai fundamental ajaran Islam sebagai landasan utama dalam pembentukan karakter dan peradaban manusia.